(untitled) (The Review of Diabetic Studies, 2025)
To study and to Identify & Classify children presented with first onset Unprovoked seizure, atypical febrile seizure and to correlate with EEG and Neuroimaging findings. Subject and methods – Data collected from case records of patients admitted with unprovoked seizures between age group 6 months to 5 yrs between 2022-2023 were included in this study. Results – In 100 children in the age group 6 months – 5 years admitted with first onset afebrile seizure and atypical febrile seizure were reviewed. Out of these children less than 2yrs are more commonly affected (52 %) and males are more commonly affected (64 %), family history of seizures is seen in 24 %, Children with history of consanguineous marriage are 13 % In this study children with generalized seizure are 46 % abnormal EEG seen in 37 % and 24 % has abnormal Neuroimaging, both EEG and Neuroimaging are abnormal in 53 %. In Partial seizures (22%), abnormal EEG and Neuroimaging is seen in 64% of children and 86% of children with abnormal EEG had abnormal neuroimaging. Conclusion – There is strong significant correlation between EEG and Neuroimaging in both generalized and partial seizures hence all children with first unprovoked /afebrile seizure should always be evaluated with neuroimaging and EEG